2014
DOI: 10.56431/p-x30728
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Herbicide (Quizalofop-p-Ethyl) on Growth, Photosynthetic Pigments, Enzymes and Yield Responses of Blackgram (<i>Vigna mungo</i> L.)

Abstract: The recent experiment was conducted to assess the effect of herbicide (quizalafop-p-ethyl) on growth, photosynthetic pigments, enzymes and yield of Black gram (Vigna mungo L.) during the summer season 2013-2014. This experiment comprised black gram (variety ADT 3) and different concentrations of herbicide (quizalafop-p-ethyl) treatments compared with control. Reduction in growth, photosynthetic pigments, enzymes and yield parameters were observed with 0.5 % herbicide application followed by 1 %, 1.5 % and 2 %,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Quizalofop induced genotoxic effects on the root cells of different plants such as faba bean and sunflowers (Karaismailoğlu et al, 2013;Çelik et al, 2022). Mahakavi et al (2014) also indicated the negative effects of quizalafop on enzymes, photosynthetic pigments, growth, and yield of Vigna mungo L. crop.…”
Section: I-grass Weed Control Experimentmentioning
confidence: 94%
“…Quizalofop induced genotoxic effects on the root cells of different plants such as faba bean and sunflowers (Karaismailoğlu et al, 2013;Çelik et al, 2022). Mahakavi et al (2014) also indicated the negative effects of quizalafop on enzymes, photosynthetic pigments, growth, and yield of Vigna mungo L. crop.…”
Section: I-grass Weed Control Experimentmentioning
confidence: 94%